The Value of a Rapid Test of Human Regulatory T Cell Function Needs to be Revised - Wendering, Desiree J.; Amini, Leila; Schlickeiser, Stephan; Reinke, Petra; Volk, Hans-Dieter; Schmueck-Henneresse, Michael (Frontiers in Immunology, 2019)
CD4+CD25+FoxP3+ human regulatory TCELLS (TREG) are promising candidates for reshaping undesired immunity/inflammation by adoptive cell transfer, yet their application is strongly dependent on robust assays testing their functionality. Several studies along with first clinical data indicate TREG to be auspicious to use for future cell therapies, e.g. to induce tolerance after solid organ transplantation. To this end, TREG suppressive capacity has to be thoroughly evaluated prior to any therapeutic application. A 7 hour-protocol for the assessment of TREG function by suppression of the early activation markers CD154 and CD69 on CD4+CD25- responder TCELLS (TRESP) upon polyclonal stimulation via CD3/28-coated activating microbeads has previously been published. Even though this assay has since been applied by various groups, the protocol comes with a critical pitfall, which is yet not corrected by the journal of its original publication. Our results demonstrate that the observed decrease in activation marker frequency on TRESP is due to competition for CD3/28-coated microbeads as opposed to a TREG-attributable effect. Of note, even non-TREG/effector TCELLS showed suppression of activation markers when following the previously published protocol. Hence, a short-term functional assay accepted as a release criterion for TREG cell products determining the suppressive capacity of conventional T cells displays competitive TCELL receptor and CD28 engagement and not TREG suppressive function.